2020
DOI: 10.17159/0379-4350/2020/v73a10
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Zeolites Produced by Ultrasonication of Coal Fly Ash/NaOH Slurry Filtrates

Abstract: Studies were conducted to determine if crystalline zeolites could be obtained from the filtrates of coal fly ash (CFA)/NaOH slurries through sonication. The CFA/NaOH slurries were obtained by aging CFA in 3 M NaOH for 24 h at 50°C using a solid/ liquid (S/L) ratio of 15 g/120 mL. FT-IR studies indicated that the 'Lo' regime ultrasonicated zeolite had higher intensities than that of the 'Hi' frequency ultrasonicated zeolite. The bands associated with the 'Lo' regime ultrasonicated zeolite were observed at 1066 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Li et al [62] have prepared a high-quality MER-rich product from coal fly ashes by KOH direct conversion method under optimal activation conditions. Mokgehle et al [63] have obtained GIS product from the ultrasonication of coal fly ash/NaOH slurry filtrates. It seems that MER phase is easy to be formed in the KOH-rich condition and GIS phase is inclined to the produced in the NaOH-rich condition from the same original materials.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [62] have prepared a high-quality MER-rich product from coal fly ashes by KOH direct conversion method under optimal activation conditions. Mokgehle et al [63] have obtained GIS product from the ultrasonication of coal fly ash/NaOH slurry filtrates. It seems that MER phase is easy to be formed in the KOH-rich condition and GIS phase is inclined to the produced in the NaOH-rich condition from the same original materials.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the -OH group from Si-OH was also proven by the absorption wave numbers of 1640.53 and 1446.67 cm -1 , which showed that there was a -OH bending vibration from Si-OH. The appearance of spectra at around 3019.69 cm -1 and 1640.53 cm -1 , which showed stretching vibrations and bending vibrations of water molecules in zeolite, was evidence of the formation of zeolite through an alkaline hydrothermal process 26 .…”
Section: Ftirmentioning
confidence: 96%